Family carers' perspectives of managing activities of daily living and use of mHealth applications in dementia care: A qualitative study. Issue 23 (3rd September 2019) - Rathnayake, Sarath; Jones, Cindy; Calleja, Pauline; Moyle, Wendy
Abstract: Aim: To examine the needs, barriers and challenges experienced by family carers of people with dementia concerning the management of their care recipients' functional disabilities, and their experiences and opinions of using mobile health (mHealth) applications in health information seeking. Background: Functional disability is a significant problem among people with dementia and management can be challenging for family carers. Evidence suggests that mHealth applications can support knowledge needs of patients and families. Design: A qualitative descriptive exploratory study. Methodology: In‐depth interviews were conducted with a purposive sample of family carers using a semi‐structured interview guide. An inductive thematic analysis method was used. The COREQ reporting guideline was followed. Results: Five spousal and five child carers participated in this study. Four key themes were identified: (a) Challenges faced that contribute to psychological distress and burden; (b) Essential role of support systems in dementia care; (c) Information and educational needs of family carers, and (d) Experiences and attitudes of mHealth applications as an educational and supportive resource. Conclusion: Providing functional care is demanding, challenging and stressful, and leads to carer burden. The complexity of dementia is a barrier in the organisation of functional care and access to a support network is vital to care provision. The information needs of family carers can potentially be addressed through an mHealth application. Relevance to clinical practice: This study provides important information on family carers' needs, and the barriers and challenges related to functional care for people with dementia. Findings from this study can assist nurses and other health professionals in the planning of educational and supportive programs for family carers. Furthermore, the use of mHealth applications could positively contribute to the delivery of these programs.